Digitalisasi Koperasi dan Partisipasi Pemuda: Inovasi Menuju Masa Depan Ekonomi Inklusif - Christian Barus, Gary; Rossenberg Mikhail Christison Aritonang, Steven; Irawan, Dandan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2026)
According to Law No. 25 of 1992 concerning Cooperatives, cooperatives are business entities based on family principles and are expected to be the pillars of the Indonesian economy. In reality, cooperatives face challenges related to digitalization and low interest from the younger generation, often deeming their role archaic, outdated, and outdated. This study aims to emphasize that digitalization is not merely technical modernization, but rather a transformational strategy capable of revitalizing the cooperative spirit and making it relevant to the younger generation. This research method uses a qualitative approach with secondary data analysis from field visits to the International Cooperative Conference 2025 (ICC 2025), as well as interviews and discussions with cooperative activists from ICC 2025 participating countries. This study found that the adoption of digital technology encourages youth participation in various aspects, from membership management, marketing innovation, to the creation of new community-based products. The results show that digitalization not only accelerates services and expands market access, but also strengthens cooperatives as an inclusive economic instrument that provides equal space for all levels of society. Moreover, digitalization opens up innovation space for youth through new roles in cooperative management, marketing, and product development. With youth involvement, cooperatives have the potential to transform into adaptive, competitive, and future-oriented collaborative ecosystems as a platform for cross-generational collaboration towards an inclusive and sustainable economy. Keywords: Digitalization, Cooperatives, Youth, Inclusive Economy